Multiplexed promoterless gene expression with CRISPReader - Zhan, Hengji (Genome Biol, 2019)
BACKGROUND: Genes are comprised of DNA codes and contain promoters and other control elements for reading these codes. The rapid development of clustered regularly interspaced short palindromic repeats (CRISPR) technology has made possible the construction of a novel code-reading system with low dependency on the native control elements. RESULTS: We develop CRISPReader, a technology for controlling promoterless gene expression in a robust fashion. We demonstrate that this tool is highly efficient in controlling transcription and translation initiation of a targeted transgene. A notable feature of CRISPReader is the ability to “read” the open reading frames of a cluster of gene without traditional regulatory elements or other cofactors. In particular, we use this strategy to construct an all-in-one AAV-CRISPR-Cas9 system by removing promoter-like elements from the expression cassette to resolve the existing AAV packaging size problem. The compact AAV-CRISPR-Cas9 is also more efficient in transactivation, DNA cleavage, and gene editing than the dual-AAV vector encoding two separate Cas9 elements, shown by targeting both reporter and endogenous genes in vitro and in vivo. CONCLUSIONS: CRISPReader represents a novel approach for gene regulation that enables minimal gene constructs to be expressed and can be used in potential biomedical applications. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13059-019-1712-5) contains supplementary material, which is available to authorized users.